May maternal lifestyle have an impact on neonatal glucose levels?. (February 2016) - Hoirisch-Clapauch, Silvia; Porto, Maria Amelia S.; Nardi, Antonio E.
Abstract: Neonatal glucose levels correlate negatively with umbilical cord levels of C-peptide, a polypeptide secreted with insulin. In other words, neonatal hypoglycemia results from excessive insulin secretion from fetal/neonatal beta cells. Given that insulin causes fat to be stored rather than to be used for energy, one would expect that chronic hyperinsulinemia would result in large-for-gestational-age neonates. The finding that many small-for-gestational-age neonates have hypoglycemia suggests that the stimulus for insulin production occurs close to delivery. We postulated that a potent stimulation of maternal insulin production close to delivery would also provide a potent stimulus for fetal and neonatal insulin production, causing neonatal hypoglycemia. This study has evaluated 155 mothers with markers of excessive insulin production (such as acanthosis or grade III obesity), or with situations characterized by increased insulin requirements (such as an invasive bacterial infection or use of systemic corticosteroid within a week before delivery; or sedentariness or high-carbohydrate intake within 24 h before delivery) and their 158 neonates who were screened for glycemic levels at 1, 2 and 4 h after birth. The minimum glucose level was correlated to the maternal parameters, and to classical predictors of neonatal hypoglycemia, such as low-birth weight and preterm delivery. The only independent predictors were sedentariness and high-carbohydrate intake within 24 h before delivery. The risk of neonatal hypoglycemia increased five-fold with sedentariness, 11-fold with high-carbohydrate intake, and 329-fold with both risk factors. The risk of neonatal hypoglycemia seems to be highly influenced by maternal lifestyle within 24 h before delivery. Controlled randomized trials may help determine whether a controlled carbohydrate diet combined with regular physical activity close to delivery can prevent neonatal hypoglycemia and all its severe complications to the newborn.